A Methodological Framework for Prioritising Infrastructure Investment. (December 2016) - Andres, Luis; Biller, Dan; Dappe, Matias Herrera
Policy makers are often confronted with a myriad of factors in the investment decision-making process. This issue is particularly acute in infrastructure decisions since these often involve large sums and lock-in technologies. In regions and countries where the infrastructure access gap is large and public budgets severely constrained, the importance of considering the different facets of the decision-making process becomes even more relevant. This is the case for South Asia. This article presents the infrastructure access gap in South Asia and discusses the impacts that this gap has in South Asian economies. It examines the links between the infrastructure and economic growth and infrastructure and welfare/poverty. The article reviews different methodologies to measure these impacts and hence serve as mechanisms to establish priorities. Finally, the article presents a methodology to holistically equate trade-offs among different policy objectives per key infrastructure sectors.